PENGARUH PENGGUNAAN VIDEO ANIMASI TERHADAP PEMAHAMAN MAHASISWA MENGENAI KONSEP DINAMIKA GERAK DALAM BIOMEKANIKA - Syafruddin, Akbar; Nur Indah Atifah Anwar (FKIP Palangka Raya University, 2025)
This study uses an experimental method that aims to determine the impact of using animated videos on students' understanding of the concept of motion dynamics in biomechanics courses. The research design used is a two-group pre-test and post-test design. The data collection technique is carried out by testing students' knowledge in the material of the concept of motion dynamics in biomechanics courses. The sample in this study was 2 classes determined by the simple random sampling technique. The number of samples from each class was 42 people for the experimental class and 40 people for the control class. The data analysis technique was carried out using the independent sample T test. The form of treatment carried out was by providing students with a learning model that utilized animated video media for 4 meetings in the material of the concept of motion dynamics in biomechanics courses. The results of the hypothesis test in the table above show a Sig. value of 0.000 <0.05. So it can be said that there is a difference between the data from the experimental group and the control group. Furthermore, the mean value of the experimental group is 92 and the mean value of the control group is 89, so the mean difference between the experimental and control groups is 3. So it can be concluded that the use of animated videos has an effect on increasing students' understanding of the concept of motion dynamics in biomechanics.